1 + i + i ² + i ³ + i ⁴ + i ⁵ = 1 + i + i ² (1 + i + i ² + i ³)
… = 1 + i + i ² (1 + i + i ² (1 + i ))
… = 1 + i + (-1) (1 + i + (-1) (1 + i ))
… = 1 + i + (-1) (1 + i - 1 - i )
… = 1 + i
Alternatively, notice that
1 - i ⁶ = (1 - i ) (1 + i + i ² + i ³ + i ⁴ + i ⁵)
so that
1 + i + i ² + i ³ + i ⁴ + i ⁵ = (1 - i ⁶) / (1 - i )
Now, i ⁶ = (i ²)³ = (-1)³ = -1, so
1 + i + i ² + i ³ + i ⁴ + i ⁵ = (1 - (-1)) / (1 - i )
… = 2 / (1 - i )
Multiply the numerator and denominator by the conjugate of 1 - i :
… = 2 (1 + i ) / ((1 - i ) (1 + i ))
… = 2 (1 + i ) / (1² - i ²)
… = 2 (1 + i ) / (1 + 1)
… = 1 + i